Dothistroma septosporum and Dothistroma pini, the causal agents of Dothistroma needle blight, are infected by multiple viruses - Miloš Trifković; Ondřej Hejna; Anna Kuznetsova; Martin Mullett; Libor Jankovský; Leticia Botella (Virus Research)
Dothistroma septosporum and Dothistroma pini are severe foliar pathogens of conifers. They infect a broad spectrum of hosts (mainly Pinus spp.), causing chlorosis, defoliation of needles, and eventually the death of pine trees in extreme cases. Mycoviruses represent a novel and innovative avenue for controlling pathogens. To search for possible viruses hosted by Dothistroma spp. we screened a subset of isolates (20 strains of D. septosporum and one D. pini) originating from the Czech Republic, Slovenia, Italy, Austria and Ireland for viral dsRNA segments. Only five of them showed the presence of dsRNA segments. A total of 21 fungal isolates were prepared for total RNA extractions. RNA samples were pooled, and two separate RNA libraries were constructed for stranded total RNA sequencing. RNA-Seq data processing, pairwise sequence comparisons (PASC) and phylogenetic analyses revealed the presence of thirteen novel putative viruses with varying genome types: seven negative-sense single-stranded RNA viruses, including six bunya-like viruses and one new member of the order Mononegavirales; three positive-sense single-stranded RNA viruses, two of which are similar to those of the family Narnaviridae, while the genome of the third correspond to those of the family Gammaflexiviridae; and three double-stranded RNA viruses, comprising two novel members of the family Chrysoviridae and a potentially new species of gammapartitivirus. The results were confirmed with RT-PCR screening that the fungal pathogens hosted all the viruses and showed that particular fungal strains harbour multiple virus infections and that they are transmitted vertically. In this study, we described the narnavirus infecting D. pini. To our knowledge, this is the first virus discovered in D. pini.